PEMANFAATAN UBI JALAR SEBAGAI BAHAN BAKU PEMBUATAN ES KRIM DALAM MENINGKATKAN EKONOMI KELUARGA DI KAMPUNG DOMANDE - Putri Inggrid Maria Risamasu; Elisabeth Pruwo Gebze (Musamus University, 2020)
Sweet potato is one of the types of tubers that are found almost in loyal community homes in the village of Domande, Malind District. In its use, sweet potatoes are often only processed by steaming, baking and even frying. Potential sweet potato in the village of Domande is very good if it is used and processed into a variety of culinary that has economic value, one of which is ice cream. The selection of ice cream to be a processed product from sweet potatoes is because this culinary is very popular with all groups, both from the age of children to adults. Utilization of sweet potatoes into economic value ice cream products is carried out by involving young people who drop out of school in the Domande village so that they are indirectly given the opportunity to participate actively in improving the family's economy and in each line of development even though it starts from the smallest scope, namely the family.